Confederate defense of Charleston, South Carolina. - Stone, Howard L., III (Fort Leavenworth, KS : US Army Command and General Staff College, 1992)
This study investigates the defense of Charleston, South Carolina, during the American Civil War. Charleston, during this period, is unique because of the diversified nature the military operations that took place there. Combat took place both on land and on water involving fortifications, ironclads and other warships, obstructions, torpedoes, and a submarine. Amphibious, psychological, and mine warfare was practiced. This study examines why the city's defenses and military operations developed as they did. It analyses a series of operations from the Union defense of Fort Sumter through the occupation of Morris Island. The blockade is also examined. This study provides reasons for the success of the Confederate defense and failure of Union offensive actions. The story of Charleston is a good example of an effective defensive operation. Charleston was not captured but evacuated when threatened by Sherman’s army. The example of Charleston also makes a strong case for joint military planning and operations. A detailed physical description of Charleston, an explanation of marine navigation during the period, and historical precedents are also presented to enhance an understanding of the operations examined.